PENGARUH PEMANFAATAN INTERNET SEBAGAI SUMBER BELAJAR SEJARAH TERHADAP MOTIVASI BELAJAR SISWA KELAS X TKJ NEGERI 7 PEKANBARU - Asmarul Azizah (Universitas Negeri Medan, 2020)
Abstract: The Influence of the Use of the Internet as a Historical Learning Resource on Class X Student Learning Motivation in TKJ Negeri 7 Pekanbaru. The application of learning by utilizing the internet can increase student motivation. These improvements include: increasing student interest and attention to the subject matter being studied, increasing student activity in the learning process, increasing collaboration between students in carrying out learning tasks in groups, increasing student enthusiasm for learning in class during the learning process, increasing and student involvement in groups during the learning process, and increased joy in learning in the classroom. From observations in the first and second cycles obtained motivation and cognitive learning outcomes of students increased from 50% of students achieving the KKM value and after the actions in the second cycle there was an increase in motivation and student learning outcomes to 94.44% had reached the KKM value. Keywords: internet, history, motivation. Abstrak: Pengaruh Pemanfaatan Internet Sebagai Sumber Belajar Sejarah Terhadap Motivasi Belajar Siswa Kelas X TKJ Negeri 7 Pekanbaru. Penerapan pembelajaran dengan memanfaatkan internet dapat meningkatkan motivasi belajar siswa. Peningkatan tersebut meliputi: meningkatnya minat dan perhatian siswa terhadap materi bahasan yang dipelajari, meningkatnya keaktifan siswa dalam proses pembelajaran, meningkatnya kerjasama antar siswa dalam melaksanakan tugas-tugas pembelajaran dalam kelompok, meningkatnya semangat belajar siswa di kelas selama proses pembelajaran, meningkatnya dan keterlibatan siswa siswa dalam kelompok selama proses pembelajaran, dan meningkatnya rasa senang dalam belajar dikelas. Dari observasi pada siklus I dan II diperoleh motivasi dan hasil belajar kognitif siswa meningkat dari 50 % siswa mencapai nilai KKM dan setelah tindakan pada siklus II ada peningkatan motivasi dan hasil belajar siswa menjadi 94,44 % telah mencapai nilai KKM. Kata kunci : internet, sejarah, motivasi.